2017
DOI: 10.2147/tcrm.s134153
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic reliability of pediatric appendicitis score, ultrasound and low-dose computed tomography scan in children with suspected acute appendicitis

Abstract: BackgroundDiagnosis of appendicitis in children is clinically challenging. Computed tomography (CT) is the gold standard for diagnosis; however, radiation exposure early in life is a concern with this technique. Therefore, in this study, we aimed to evaluate the diagnostic reliability of low-dose CT, pediatric appendicitis score (PAS), and abdominal ultrasound (US) in children with acute appendicitis, to reach a safe diagnosis.Patients and methodsThis retrospective study was conducted on 140 children who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
(32 reference statements)
2
23
0
2
Order By: Relevance
“…In a similar type of study has been conducted in Iran, where 67 patients were examined with LRQP and underwent appendectomy, diagnostic accuracy was 72.4% after US examination of abdominal organs with a compression test (Nasiri et al, 2012). Another study using US examination had accuracy of 92%, establishing strict criteria of US (Sayed et al, 2017). However, in the present study found, US examination accuracy was lower: sensitivity 67.7%, with specificity 76.9% and accuracy 71.9%.…”
Section: Discussionsupporting
confidence: 44%
“…In a similar type of study has been conducted in Iran, where 67 patients were examined with LRQP and underwent appendectomy, diagnostic accuracy was 72.4% after US examination of abdominal organs with a compression test (Nasiri et al, 2012). Another study using US examination had accuracy of 92%, establishing strict criteria of US (Sayed et al, 2017). However, in the present study found, US examination accuracy was lower: sensitivity 67.7%, with specificity 76.9% and accuracy 71.9%.…”
Section: Discussionsupporting
confidence: 44%
“…While ultrasound is a safe choice for first-line imaging in cases of suspected appendicitis due to lack of ionising radiation, 19 it is an operator-dependent imaging modality. 13 Variation of operator experience has been identified as a limiting factor of sonographic evaluation of appendicitis, 7,38 and due to its potential to cause variation of diagnostic performance between operators and across centres, it may be one of the reasons for the low sensitivity of ultrasound to differentiate between perforated and non-perforated appendicitis. 39 Two of the retrospective studies assessed inter-observer agreement among the radiologists reviewing the sonographic findings of appendiceal perforation.…”
Section: Operator-dependency Limitationsmentioning
confidence: 99%
“…[6][7][8] Perforation is typically defined as a hole in the appendix wall or the presence of an extraluminal appendicolith in the abdominal cavity, 3 and is important to identify because of its association with increased complications and morbidity. 9 Computed tomography (CT) has excellent diagnostic accuracy for identifying acute appendicitis [10][11][12][13] and can differentiate between non-perforated and perforated appendicitis. [14][15][16] However, there are concerns that the ionising radiation exposure of CT increases risk of cancer, 17 especially in children.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations